ANALISIS PENGEMBANGAN KOTA PEKALONGAN SEBAGAI SALAH SATU KAWASAN ANDALAN DI JAWA TENGAH - Choliq Sabana (Fakultas Ekonomi Universitas Pekalongan, 2015)
The aim of this research is to identify characteristics of Pekalongan city as priority zone. Those characteristicsare high growth and high income, leading sector, and interrelatedness economy with other region. For thispurpose, it’s used by analysis tool : Klassen Tipology, Location Quotient ( LQ ), Growth Ratio Model (GRM),Overlay, Shift Share, and Gravity Model.The results show that Pekalongan city in the classify low growth and high income region. By using LQ analysisthat in Pekalongan City there are almost all sectors in Pekalongan City are leading sectors, except agriculturesector and industry sector, but by using overlay and shift share analys show those true sectors have competitiveadvantage and specialize two sectors only, they are trading sector and finance sector. By using gravity model todescribe there are belong to related fervent by closeness trend increasing expanded as miter cooperate in areadeveloping, they are Batang Regency and Pekalongan Regency. By all account have done. They can be takenconclusion that’s decisioned Pekalongan city as Region key or less appropriate. Although if were observerd bysome leading sector or there are related economy among decision area Pekalongan City it’s appropriate.Keywors: Priority zone, Klassen Tipology, Overlay, Gravity Model